A Study of Cancer of Ovaries among Women and it’s Linked with the Stem Cells present in Body: A Review - Saira John, Nickson Subeston Anthony, Shees Bazr Bhatti, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Ovarian cancer (OC) is the seventh most commonly diagnosed cancer among women in the world. A woman’s lifetime risk of developing OC is 1 in 75, and her chance of dying of the disease is 1 in 100.Cells which initiate cancer cells in the body are somehow known as stem cells. Objective: The objective of this review was to evaluate the published literature on epidemiologic risk factors for ovarian cancer among women and it’s linked with the stem cells present in the body. Material and methods: A review of literature search was conducted in PubMed and Scopus. Studies comparing ovarian cancer among women and its linked with the stem cells present in the body were included. Results: Eight of 94 articles met the inclusion criteria. The articles revealed that there are no rules to separate out the cells which are spreading tumor cells or in short from this research they said that we are not able to separate them out but we can clarify the issue that either they are spreading this deadly disease or not. Stem cells are not linked with ovarian cancer. Conclusion: It is concluded that phonetically both cancer cells and stem cells are not same. They are showing their opposite impacts. In this study we have seen that first they initiate from a single cell and then start replicating and make groups. There are many other ways through which tumor cells can generate themselves so it is not easy to say that they are growing from stem cells. Keywords: Ovarian cancer, Stem cells and Women